PELAKSANAAN FUNGSI PENGAWASAN DPRD TERHADAP PENGGUNAAN ANGGARAN APBD DI PROVINSI SULAWESI SELATAN - Sukarman (Jurnal Ilmiah Administrasita', 2014)
This research aims to (1) to analytical and know the Implementation Monitoring Function Parliament Under The Budget year 2013 Implementation in the Province of South Sulawesi. (2) to know determine the factors that affect Implementation Monitoring Function Parliament Under The Budget year 2013 Implementation in the Province of South Sulawesi.The method used in this research is a descriptive analytical and empirical, data sources are the primary data and secondary data,engineering data collection through interviews, literature studies, archives and documents. Analysis of data obtained using non profanity sampling method (no random) the group of 15 people the member of parliament, and the group of 3 people eksekutive, and the group of 2 people NGOs.This observational result points out that: supervisory logistic performing Region Parliament to APBD'S Budget Purpose at subtracted South Sulawesi Province effective. Factor-factor that regards is SDM'S quality, Commitment and Accountability and Marks Sense Parpol's Interference.